Pakubuwana IV Sebagai Maecenas: Tinjauan Kritis Beberapa Teks Pengětan Sejarah Wayang - Rudy Wiratama (Jumantara: Jurnal Manuskrip Nusantara, 2021)
Pakubuwana IV (reigned 1788-1820) despite of his popularity in political history and literature, also considered a founder of the iconography and performance principles of Surakartanese style wayang kulit (shadow puppet) as written in the pengětan (i.e. “memorial”) texts, particularly in Surakarta version. The pengětan text genre as a literary work was rarely studied and only taken for granted by the puppeteers in Java because of its legitimative and semi-mythological nature. It leads to an uncertainty about the facts contained inside and causing a dispute in the society. This article would objectively discover about “how was the real influence of Pakubuwana IV in the Surakartanese style wayang kulit’s history and development?” and “did pengětan text were able to provide objective facts in minor field of historiography, including art history?”  This article aims to discover the real influence of Pakubuwana IV in Surakarta-style wayang kulit history and development through textual approach using pengětan texts comparison as the its method, along with contextual approach with the contemporary wayang artefacts. The result of this research shows that Pakubuwana IV gave a crucial contribution in Surakarta-style wayang kulit. On the other hand, critical readings of pengětan manuscripts are needed to analyze the historical and political nature on its narrative so it could give a much comprehensive facts dealing with art and culture historiography.